The Swiping Desire: Intimacy, Libidinal Capitalism, and the Digital Subject in The Tinder Swindler - Naim, Chanif Ainun (Masyarakat: Jurnal Sosiologi, 2025)
This article examines how dating applications operate as libidinal infrastructures that restructure and commodify intimacy within platform capitalism, using The Tinder Swindler as a cultural case study. Employing a visual-narrative approach within the framework of Critical Discourse Analysis, the film is analyzed to reveal the structural exploitation of user affect and desire. Grounded in Lacanian psychoanalysis and Baudrillard’s simulation theory, the study argues that these platforms capitalize on the subject’s ontological lack (manque) which fuels desire as the desire for the Other’s desire. This psychic lack sustains a perpetual pursuit of recognition that can never be fulfilled. The swindler’s hyper-curated persona, a Baudrillardian simulacrum, demonstrates how the platform’s logic can be used to manipulate emotional vulnerability. Tinder transforms yearning into a site of value extraction through cyclical, addictive engagement. The findings show that users perform affective labor, such as curating profiles, optimizing self-presentation, and managing emotional availability, while behavioral data is continuously harvested. Ultimately, this article contends that the digital subject must reclaim the opacity of desire and resist the imperative of constant affective transparency as a form of critical refusal against algorithmic governance over the intimate self.